ANALISIS DAMPAK KEKERASAN SEKSUAL TERHADAP ANAK DI KECAMATAN PAUH KOTA PADANG - Fajriansyah, Muhammad Rizky (Ensiklopedia Sosial Review, 2019)
Sexual violence in various countries in the world was increasing every year. The data released by national commission for child protection shows that violence against children to school rises by 2015. There are 2.898 reports of violence against children , 62 percent of them constitutes a crime sexual. Method : This study uses qualitative methods in Pauh District, Padang City. Data was collected through in-depth interviews. The research informants were selected by purposive sampling of sexual violence, families and figures who play a role in overcoming sexual violence in children based on records from the record police in 2015. Result : Based on the results of research that sexual violence on child resulting in children to shy, morose, and inactive in the classroom. The impact of sexual violence not only at the victim but also parents from sons to feel ashamed and shrink from neighbors around and spend money which is large for a case that occurred to their children. Knowledge of people who participated in sexual prevention of sexual assault on child relative less. Conclusions : The impact of sexual violence disturbs teaching or habits and the activities and family oil the future .The need for the role of family , tokoh-tokoh that mempenyai the role of sexual violence against reduction of religious leaders , community leaders and paramedics nearest